Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3831/kpi.2012.15.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Effects of Bee Venom Pharmacopuncture According to the Treatment Method for Knee Osteoarthritis

Abstract: Objectives:The purpose of this study is to compare the effects of bee venom pharmacopuncture (BVP) therapy according to the methods used to treat knee osteoarthritis (OA): intra-acupoint combined with intra-articular injection, intra-acupoint injection, and intra-articular injection.Methods:A total of 69 patients were recruited by the Department of Acupuncture & Moxibustion at Dong- Eui Oriental University Hospital from February 1 to July 23, 2012. The patients were assigned to 3 groups: the first group with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…After 12 weeks, the BV biotherapy group showed a remarkable improvement over the control group in Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain scores [ 87 ]. Another comparative study revealed that a combination of intra-articular injection with intra-acupoint injection was more effective than conservative treatments for osteoarthritis of the knee [ 88 ].…”
Section: Clinical Applications and Mechanism Of Bv Injectionmentioning
confidence: 99%
“…After 12 weeks, the BV biotherapy group showed a remarkable improvement over the control group in Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain scores [ 87 ]. Another comparative study revealed that a combination of intra-articular injection with intra-acupoint injection was more effective than conservative treatments for osteoarthritis of the knee [ 88 ].…”
Section: Clinical Applications and Mechanism Of Bv Injectionmentioning
confidence: 99%
“…Moreover, melittin itself has been shown to induce allergic reaction and inflammation under certain conditions [46, 47]. Nevertheless, the anti-inflammatory properties of BV and melittin described in the previous literature suggest therapeutic benefit [48, 49] and BV pharmacopuncture is widely used in Korean medicine practice [50, 51]. The authors have also conducted a clinical trial comparing the anti-inflammatory and local adverse effects and allergic reaction to BV and eBV, which is currently submitted to be considered for publication.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, as result of increasing investigation worldwide, the usefulness of BV has been reported for several diseases and pathologic contexts (Table 2), in studies performed in vitro and in vivo, in animal models or enrolling humans. Among other settings, the effects of BV were demonstrated in multiple sclerosis and Parkinson's disease (Ostrovsky and Ehrlich, 2018), dementia (Silva et al, 2015), atherosclerosis (Lee and Bae, 2016), osteoarthritis (Lee et al, 2012), human immunodeficiency virus (HIV) (Jallouk et al, 2014), periodontitis (Gu et al, 2019), Diabetes mellitus (Hossen et al, 2017) and rheumatoid arthritis (Son et al, 2007;Brito et al, 2018). The effects of BV and its isolated bioactive compounds have also been described in several types of solid cancer like breast, ovarian, bladder, lung, liver and prostate, as well as on hematologic malignancies (Moga et al, 2018).…”
Section: Therapeutic Applications Of Bee Venom In Human Healthmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis Lee and Bae (2016) [in vivo, animal models] Anti-ageing Choi et al (2015) [in vivo, humans;in vitro]; Han et al (2013a) [in vivo, humans;in vitro]; Tusiimire et al (2015) [in vitro]; Han et al (2015) [in vivo, humans;in vitro]; Lee et al (2015) [in vitro] Anti-arthritic Lee et al (2012); Wang et al (2002); Jeong et al (2015); Son et al (2007) [all studies performed in vivo, in humans]; Anti-dandruff Prakash and Bhargava (2014) A. Pascoal, et al Food and Chemical Toxicology 134 (2019) 110864 Han et al (2013a) observed that cosmetics containing purified BV had a better efficiency in reducing microorganisms' concentration and the number of skin lesion, suggesting that purified BV could be a good candidate for developing new formulations for acne vulgaris treatment.…”
Section: Effects Of Bee Venom Referencesmentioning
confidence: 99%